2014
DOI: 10.3390/pathogens3030743
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Related to Biofilm Formation in Klebsiella pneumoniae

Abstract: The Gram-negative opportunistic pathogen, Klebsiella pneumoniae, is responsible for causing a spectrum of community-acquired and nosocomial infections and typically infects patients with indwelling medical devices, especially urinary catheters, on which this microorganism is able to grow as a biofilm. The increasingly frequent acquisition of antibiotic resistance by K. pneumoniae strains has given rise to a global spread of this multidrug-resistant pathogen, mostly at the hospital level. This scenario is exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
189
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(201 citation statements)
references
References 96 publications
4
189
2
6
Order By: Relevance
“…The most common healthcare-associated infections caused by this strain involves the urinary tract infection, wound infections, lungs infection, colonisation of intravascular devices, surgical site and soft tissues infection and subsequent bacteraemia. (13) In the prevailing study, it was found that K. pneumoniae was maximum isolated from the endotracheal tube tips and the tracheostomy tube tips followed by A. baumannii and P. aeruginosa. Since these organisms are highly linked as oral pathogens their association with biofilm formation on these tips can be a reason behind their high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The most common healthcare-associated infections caused by this strain involves the urinary tract infection, wound infections, lungs infection, colonisation of intravascular devices, surgical site and soft tissues infection and subsequent bacteraemia. (13) In the prevailing study, it was found that K. pneumoniae was maximum isolated from the endotracheal tube tips and the tracheostomy tube tips followed by A. baumannii and P. aeruginosa. Since these organisms are highly linked as oral pathogens their association with biofilm formation on these tips can be a reason behind their high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, other mechanisms are involved, and further studies are required to elaborate on new concepts in the preventive measures against nosocomial K. pneumoniae infections in the future. [11] In chronic surface wounds with biofilms, the latter can be eradicated with topical bioflammacide therapy; this would not be an option for gastrointestinal disease. [12] …”
Section: Discussionmentioning
confidence: 99%
“…EO T is especially rich in α-and β-turmerone and ar-turmerone [15]. It was reported that the EO T from rhizomes had an antibacterial effect on P. vulgaris, K. pneumoniae [16,17], and B. cereus and B. subtilis [18] but did not affect S. typhimurium, S. aureus, E. coli and L. monocytogenes [19,20].…”
Section: Introductionmentioning
confidence: 99%